Tourists in the Emergency Department. An Overview of presentations - Sigríður Hrönn Guðmundsdóttir 1978- (2016)
Introduction: The number of foreign tourists visiting Iceland has more than doubled since 2010. For a small nation like Iceland such rapid tourism growth puts a strain on its infrastructure including healthcare service and search and rescue squads. Purpose and goals: The object of the study was to explore the frequency and epidemiology of health issues affecting tourist. Identifying; demographic patterns, types of health problems, activities and locations involved in injuries and mode of injuries. Methods: Retrospective study using ED presentations data from Landsspítali Hospital. Sample included all foreign nationals who attended the ED from 2010-2014. 6.702 cases. Descriptive statistical analysis was used to explore relationships between variables including; reason for contact, place of occurrence, activity and mode of injury. Results: 65% increase in tourist ED presentations, although the incidence proportion rate declined same time. Tourists from the US (13%), Germany (10,8%), and the UK (10,7%), had the highest presentation volume, however tourists from Spain, and Italy, proportionately required the most frequent medical care. The most common place of injury occurrence was open nature 15,4%. Falls were by far the main cause of injury ED presentations 58%, Females particularly older ones were more likely to seek medical care due to a fall injury. Conclusions: The results from the study provided a useful overview of tourist injury and illness demographic patterns, prevalence, growth-rate, incidence rate and injury mode, which were previously unknown in Iceland, and thus the study provides valuable knowledge to the field. Bakgrunnur: Fjöldi ferðamanna sem heimsækja Ísland hefur meira en tvöfaldast frá árinu 2010. Fyrir litla þjóð eins og Ísland hefur þessi öri vöxtur haft áhrif á innviði landsinns, þar á meðal heilbrigðiskerfið og björgvunarsveitirnar. Tilgangur og markmið: Markmið rannsóknarinnar var að gera faraldsfræðilega rannsókn á heilsuvandamálum erlendra ferðamanna. Skoða tíðni veikinda og slysa, ...